2021
DOI: 10.37394/232013.2021.16.20
|View full text |Cite
|
Sign up to set email alerts
|

Geomechanical Hazards related to River Hydraulics and Remedial Measures: Selected Case Studies in India

Abstract: River science and engineering has been one of the important study areas for geologists, hydrologists and engineers. The open channel flow and associated hydraulics often initiate several geomechanical hazards including silting and scouring, meandering and migration, floods, etc. Such hazards may lead to disastrous consequences if adequate remedial measures are not undertaken by proper river training works. This paper presents selected case studies in northern and north-eastern parts of India where such hazards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…It is therefore evident that shallower sections of the river channel are characterized by high sand deposition and accumulation. This finding agrees with that by Dutta et al (2021), who found that narrow and deep sections of the river channel are characterized by high speed of the river current since they act as constrictions, a factor that promotes erosion processes as opposed to deposition. Increase in depth of a river channel is usually coupled with increasing slope angle, a factor that discourages deposition.…”
Section: River Channel Depth and Sand Abundancesupporting
confidence: 92%
See 1 more Smart Citation
“…It is therefore evident that shallower sections of the river channel are characterized by high sand deposition and accumulation. This finding agrees with that by Dutta et al (2021), who found that narrow and deep sections of the river channel are characterized by high speed of the river current since they act as constrictions, a factor that promotes erosion processes as opposed to deposition. Increase in depth of a river channel is usually coupled with increasing slope angle, a factor that discourages deposition.…”
Section: River Channel Depth and Sand Abundancesupporting
confidence: 92%
“…According to Chilikova-Lubomirova (2020), low river channel angles characterizing the convex banks encourage deposition of sand since it facilitates slow movement of water. On the other hand, Dutta et al (2021) pointed out that concave banks are characterized by active erosion, a factor that discourages deposition and accumulation of sand since the slope angles on such banks are high.…”
Section: The Role Of Slope Angles On Sand Abundancementioning
confidence: 99%
“…The increasing population in coastal localities worldwide demands enhancement of freshwater extraction in those regions initiating saltwater interface to advance towards the aquifers, producing saline water intrusion [3]. Such intrusion not only contaminates coastal fresh groundwater resources remarkably making it unsuitable for consumption for domestic, irrigation, and industry usages, but also alters the geotechnical and geohydraulic properties of the aquifer materials affecting their flow characteristics, influencing the pumping and other engineering activities [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%